Bifurcation analysis of Friedkin–Johnsen and Hegselmann–Krause models with a nonlinear interaction potential - Atas, Fatma; Demirci, Ali; Özemir, Cihangir (Elsevier BV, 2021)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Bifurcation theory for ordinary differential equations; nonlinear opinion dynamics; social networks; Dynamical systems in optimization and economics; imperfect pitchfork bifurcation; Social networks; opinion dynamics